Network pharmacology and molecular docking analyses on Lianhua Qingwen capsule indicate Akt1 is a potential target to treat and prevent COVID‐19. (3rd November 2020) - Xia, Qi‐Dong; Xun, Yang; Lu, Jun‐Lin; Lu, Yu‐Chao; Yang, Yuan‐Yuan; Zhou, Peng; Hu, Jia; Li, Cong; Wang, Shao‐Gang
Abstract: Objectives: Coronavirus disease 2019 (COVID‐19) is rapidly spreading worldwide. Lianhua Qingwen capsule (LQC) has shown therapeutic effects in patients with COVID‐19. This study is aimed to discover its molecular mechanism and provide potential drug targets. Materials and Methods: An LQC target and COVID‐19–related gene set was established using the Traditional Chinese Medicine Systems Pharmacology database and seven disease‐gene databases. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and protein‐protein interaction (PPI) network were performed to discover the potential mechanism. Molecular docking was performed to visualize the patterns of interactions between the effective molecule and targeted protein. Results: A gene set of 65 genes was generated. We then constructed a compound‐target network that contained 234 nodes of active compounds and 916 edges of compound‐target pairs. The GO and KEGG indicated that LQC can act by regulating immune response, apoptosis and virus infection. PPI network and subnetworks identified nine hub genes. The molecular docking was conducted on the most significant gene Akt1, which is involved in lung injury, lung fibrogenesis and virus infection. Six active compounds of LQC can enter the active pocket of Akt1, namely beta‐carotene, kaempferol, luteolin, naringenin, quercetin and wogonin, thereby exerting potential therapeutic effects in COVID‐19. Conclusions: The network pharmacological strategy integrates molecular docking to unravel the molecular mechanism of LQC. Akt1 is a promising drug target to reduce tissue damage and help eliminate virus infection. Abstract : A Lianhua Qingwen capsule (LQC) target and COVID‐19 related gene set is established to construct compound‐target pharmacology network. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analysis indicate the regulating effect of LQC on apoptosis, antivirus, immune defense, and inflammatory response. Protein‐protein interaction network and critical subnetworks are constructed to identify hub gene target. The most significant gene, Akt 1, is selected to perform molecular docking with active compounds of LQC. Six compounds are finally recognized as potential anti‐COVID‐19 agents.